Nondual Awareness and Minimal Phenomenal Experience - Josipovic, Zoran; Miskovic, Vladimir (Frontiers in Psychology, 2020)
Minimal phenomenal experiences (MPEs) have recently gained attention in the fields of neuroscience and philosophy of mind. They can be thought of as episodes of greatly reduced or even absent phenomenal content together with a reduced level of arousal. It has also been proposed that MPEs are cases of consciousness-as-such. Here, we present a different perspective, that consciousness-as-such is first and foremost a type of awareness, that is, non-conceptual, non-propositional, and nondual, in other words, non-representational. This awareness is a unique kind and cannot be adequately specified by the two-dimensional model of consciousness as the arousal level plus the phenomenal content or by their mental representations. Thus, we suggest that to understand consciousness-as-such, and by extension consciousness in general, more accurately, we need to research it as a unique kind.